2017
DOI: 10.1080/08039488.2017.1365379
|View full text |Cite
|
Sign up to set email alerts
|

Changes in antipsychotics and other psychotropic drugs during a 30-month lifestyle intervention among outpatients with schizophrenia

Abstract: Most patients decreased or stabilized their total dose of antipsychotic medication during the study period. Many patients were subject to antipsychotic polypharmacy. The extent of participation in the lifestyle intervention program did not correlate with the changes in dosing of antipsychotic medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…Our findings are somewhat in line with the only other study known to us that evaluated medication use after a lifestyle focused program in patients with SMI (43). In that naturalistic study, Højlund et al found a decrease in the use of antipsychotics in patients, although they found no specific association between these changes and the degree of participation in the intervention they delivered.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are somewhat in line with the only other study known to us that evaluated medication use after a lifestyle focused program in patients with SMI (43). In that naturalistic study, Højlund et al found a decrease in the use of antipsychotics in patients, although they found no specific association between these changes and the degree of participation in the intervention they delivered.…”
Section: Discussionsupporting
confidence: 92%